2021
DOI: 10.1016/j.jsps.2021.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Application of the health Belief Model to assess community preventive practices against COVID-19 in Saudi Arabia

Abstract: Background The novel coronavirus disease (COVID-19) has affected hundreds of thousands of people across more than 200 countries. As the pandemic continues, the health agencies, worldwide, are recommending strict preventive practices to avert its transmission at community scale. We sought to predict the behavior of the Saudi population for adopting community preventive practices during the COVID-19 pandemic. Methods: An online questionnaire consisting of 22 items pertaining to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 28 publications
2
18
1
Order By: Relevance
“…The HBM framework helps to predict the causes for individual decisions to adopt preventive measures that will reduce the risk of infection (19,36). A previous study in Saudi Arabia showed that HBM constructs can be used to assess community protective measures (37). In addition, HBM constructs explained 27% of the variance in COVID-19 preventive behaviors within the general population of Iran (6).…”
Section: Discussionmentioning
confidence: 99%
“…The HBM framework helps to predict the causes for individual decisions to adopt preventive measures that will reduce the risk of infection (19,36). A previous study in Saudi Arabia showed that HBM constructs can be used to assess community protective measures (37). In addition, HBM constructs explained 27% of the variance in COVID-19 preventive behaviors within the general population of Iran (6).…”
Section: Discussionmentioning
confidence: 99%
“…Syed/Nov 2021 106 Application of the Health Belief Model to assess community preventive practices against COVID-19 in Saudi Arabia.…”
Section: Participants Online Questionnairementioning
confidence: 99%
“… 920 participants Online questionnaire The authors suggested their results could prove the importance/power of the Saudi Vision (2030) represented by “the National Transformation Program on enhancing the healthcare system, facilitating access to healthcare, and integrating technology among government parties” addressed during the COVID-19 pandemic. Syed/Nov 2021 106 Application of the Health Belief Model to assess community preventive practices against COVID-19 in Saudi Arabia. 900 participants Online questionnaire The health belief model’s constructs of perceived susceptibility, severity, benefits, and cue to action can be adopted to help strengthen COVID-19 limiting behaviors and prevention programs.…”
Section: The Searched Outcomesmentioning
confidence: 99%
“…Alizadeh et al defined the COVID-19 pandemic as the greatest challenge that humanity has ever faced since the Second World War [ 2 ]. Studies have found that the spread of novel coronavirus has greatly impacted numerous people from over 200 countries [ 3 ]. Simultaneously, this epidemic has also caused a series of social, economic, and environmental impacts worldwide [ 4 ].…”
Section: Introductionmentioning
confidence: 99%